Postgraduate education in dental implantology in the United Kingdom: a review - Na Yeoun Kim; Sami Stagnell (SpringerOpen, 2018)
Abstract Background The qualified dentists in the United Kingdom (UK) are not expected to be competent in practising implant dentistry without further training in the subject and there is now greater emphasis on postgraduate training in Dental Implantology. There are three main education pathways at present, yet their training standards vary significantly. This study aims to identify UK postgraduate academic qualifications and continuing professional development (CPD) courses available in the field of Dental Implantology and evaluates the current standard of the postgraduate training programmes against the Training Standards in Implant Dentistry (TSID) guidelines from Faculty of General Dental Practice (FGDP (UK)). Results There were eight master level courses with varying types of qualification and study mode. The mean duration and tuition fee of the courses were 2.50 years and £23,635.50 per course, respectively. There were eight postgraduate diploma part-time courses with the mean duration of 2.00 years, and the mean tuition fee of £20,177.08 per course. The mean duration for two postgraduate certificate part-time courses was 1.00 year with the mean tuition fee of £9441.50. However, there were no full-time study options for these courses. All courses identified stated their compliance with TSID guidelines. The mean duration for 13 CPD courses identified was 0.94 years and all courses were delivered in a part-time mode. Eleven of these courses were verifiable CPD courses, and two courses were providing certificates only. Not all courses were fully compliant with TSID guidelines. Ten courses clearly stated that they provide mentoring for implant placements, and the number of supervised cases varied considerably between 1 and 50. Conclusion Development of FGDP (UK) TSID guidelines has led to a significant improvement in the quality of postgraduate education in Dental Implantology in the UK. However, not all courses are fully compliant with these guidelines and the provision of mentoring for implant placements also needs to be standardised. Quality-assured training is directly related to patient safety, and therefore all UK postgraduate training pathways must ensure their compliance with the current guidelines.